Traditional Chinese exercises on pain and disability in middle-aged and elderly patients with lumbar disc herniation: a systematic review and meta-analysis of randomized controlled trials - Zhang, Weiye; Wang, Gewen; Xie, Rong; Zhan, Jiawen; Zhu, Liguo; Wan, Chunyou; Xie, Hualong; Cai, Chuhao; Du, Yuxuan (Frontiers in Medicine, 2023)
Background Traditional Chinese exercises (TCEs) have played a significant role in treating various diseases. However, there is limited research assessing the efficacy of TCEs in treating Lumbar disc herniation (LDH). This study aimed to systematically evaluate the effects of four commonly used TCEs (Baduanjin, Yijinjing, Taichi, and Wuqinxi) on pain and disability in elderly patients with LDH. Objectives To assess the quality of relevant randomized controlled trials (RCTs) to provide evidence support for the treatment of LDH. Methods RCTs were identified through eight databases. Meta-analysis and trial sequence analysis (TSA) were conducted using RevMan 5.4, Stata 17.0, and TSA 0.9. Results A total of 22 RCTs, involving 1931 patients, were included in the analysis. TCEs exhibited a superior effectiveness in treating LDH compared to the control group. However, the TSA analysis suggested the possibility of false positives, indicating the need for more high-quality RCT evidence. Nevertheless, TCEs showed reliable results in significantly improving the VAS score and JOA score of LDH patients. Conclusion Current evidence indicates that the four TCEs have advantages in treating LDH in middle-aged and elderly individuals. However, considering the limitations of this study, we need to exercise caution in drawing conclusions, and further research is required to validate these findings. Systematic Review Registration http://www.crd.york.ac.uk/PROSPERO, identifier [CRD42023431633].